Employing Artificial Intelligence Tools to Develop Islamic Scientific Research - Al Roshdi, Aaisha Salim; Awae, Fareed; Yussuf, Ahmad (Journal of Islamic Educational Research, 2025)
This article aims to highlight the role of artificial intelligence in improving the quality of Islamic scientific research, as it starts by introducing the concept of artificial intelligence and its vital role in the development of Islamic university education, then it deals with concepts related to scientific research and the enormous importance of employing artificial intelligence tools in disciplines such as the fundamentals of jurisprudence and analysis of hadith, then the article then deals with the uses of artificial intelligence in the field of Islamic research, as well as referring to the most important tools of artificial intelligence In Islamic academic research, it also discusses the most important challenges facing the application of AI tools in this field, including critical ethical and jurisprudential challenges, such as preserving the role of human ijtihad (independent reasoning), transparency in algorithmic interpretations of sacred texts, and ensuring impartiality in the analysis of religious texts. The research concludes that AI technologies represent applications with a profound impact and effectiveness in improving the quality of Islamic scientific research, provided that a supportive environment is provided that Shariah-compliant applications are provided for the application of these technologies and training students and researchers to use them effectively and ethically.